Mechanical Strength and Analysis of Fracture of Titanium Joining Submitted to Laser and Tig Welding - Gabrielli Piveta, Ana Claudia [UNESP] (2012)
This study compared the tensile strength and fracture mechanism of tungsten inert gas (TIG) welds in cylindrical rods of commercially pure titanium (cp Ti) with those of laser welds and intact samples. Thirty dumbbell-shaped samples were developed by using brass rods as patterns. The samples were invested in casings, subjected to thermal cycles, and positioned in a plasma arc welding machine under argon atmosphere and vacuum, and titanium was injected under vacuum/pressure. The samples were X-rayed to detect possible welding flaws and randomly assigned to three groups to test the tensile strength and the fracture mechanism: intact, laser welding, and TIG welding. The tensile test results were investigated using ANOVA, which indicated that the samples were statistically similar. The fracture analysis showed that the cpTi samples subjected to laser welding exhibited brittle fracture and those subjected to TIG welding exhibited mixed brittle/ductile fracture with a predominance of ductile fracture with the presence of microcavities and cleavage areas. Intact samples presented the characteristic straightening in the fracture areas, indicating the ductility of the material.